OPTIMIZATION OF CUTTING PARAMETERS IN MILLING OPERATION TO IMPROVE SURFACE FINISH OF EN 31 (International Journal of Engineering Sciences & Management Research, 2016)
Present work includes understanding the effects of various milling parameters such as spindle speed, feed rate, depth of cut and coolant flow on the surface roughness (Ra) of finished products. The experimental plan was based on Taguchi’s technique including L9 orthogonal array with four factors and three levels for each variable and studying the contribution of each factor on surface roughness. The experiments were conducted on EN31 material on CNC vertical milling machine using carbide inserts. The analysis of mean and variance technique is employed to study the significance of each machining parameter on the surface roughness. The results indicated that cutting speed with the contribution of 60.69% is the most important parameter in controlling the surface roughness, followed by spindle speed. The optimal parameters for surface roughness is obtained as spindle speed of 1150 rpm, feed rate of 175 mm/min, 1.0 mm depth of cut, 20 lit/min coolant flow.